Weak gravitational lensing by voids - Amendola, Luca; Frieman, Joshua A.; Waga, Ioav (Monthly notices of the Royal Astronomical Society, 1999)
We consider the prospects for detecting weak gravitational lensing by underdensities (voids) in the large-scale matter distribution. We derive the basic expressions for magnification and distortion by spherical voids. Clustering of the background sources and cosmic variance are the main factors that limit in principle the detection of lensing by voids. We conclude that only voids with radii larger than ∼100 h−1 Mpc have lensing signal-to-noise ratio larger than unity.
Gesehen am 20.11.2017